“High-Risk Breast Cancer Screening in BRCA1/2 Carriers Leads to Early Detection and Improved Survival After a Breast Cancer Diagnosis” - Shraga, Shay; Grinshpun, Albert; Zick, Aviad; Kadouri, Luna; Cohen, Yogev; Maimon, Ofra; Adler-Levy, Yael; Zeltzer, Galina; Granit, Avital; Maly, Bella; Carmon, Einat; Meiner, Vardiella; et al. (Frontiers in Oncology, 2021)
Background: Germline BRCA1/2 pathogenic variant (PV)carriers have high lifetime risk of developing breast cancer and therefore subjected to intense lifetime screening. However, solid data on the effectiveness of high-risk screening of the BRCA1/2 carrier population is limited. Patients and methods: Retrospectively, we analyzed 346 women diagnosed with breast tumors. Patients were divided according to the timing of BRCA1/2 PVrecognition, before (BRCA-preDx awareness , N = 62) or after (BRCA-postDx awareness group, N = 284) cancer diagnosis. Results: Median follow-up times were 131.42 and 93.77 months in the BRCA-preDx awareness and BRCA-postDx awareness groups, respectively. In the BRCA-preDx awareness group, 78.7% of the patients had invasive tumors and 21.3% were diagnosed with pure ductal carcinoma in situ. In contrast, in the BRCA-postDx awareness group over 93% of women were diagnosed with invasive cancer and only 6.4% had in situ disease. The mode of tumor detection differed significantly between the groups: 71.9% in the BRCA-postDx awareness group and 26.2% in the BRCA-preDx awareness group were diagnosed after personally palpating a lump. Tumor size and nodal involvement were significantly more favorable in the BRCA-preDx awareness group. T stage was significantly lower in the BRCA-preDx awareness group: 54.84% at T1 and 20.96% at Tis. In the BRCA-postDx awareness group, only 37.54% were at T1 and 6.49% at Tis. The N stage was also significantly lower in the BRCA-preDx awareness group: 71% had no lymph node metastases, compared with 56.1% in the BRCA-postDx awareness group. Additionally, therapeutic procedures varied between the groups: BRCA-preDx awareness group patients underwent more breast conserving surgeries. Axillary lymph node dissection was done in 38% of women in the BRCA-postDx awareness group and in only 8.7% of the BRCA-preDx awareness group patients. Importantly, improved survival was found among patients who underwent high-risk screening (hazard ratio=0.341). Conclusions: High-risk screening facilitates the early detection of less extensive breast cancers, leads to more conservative surgeries, and potentially might improve survival.